2022
DOI: 10.3389/fmolb.2022.1089359
|View full text |Cite
|
Sign up to set email alerts
|

The role of bile acid metabolism in the occurrence and development of NAFLD

Abstract: Non-alcoholic fatty liver disease (NAFLD) has become one of the important causes of cirrhosis and liver cancer, resulting in a huge medical burden worldwide. Currently, effective non-invasive diagnostic indicators and drugs for NAFLD are still lacking. With the development of metabolomics technology, the changes in metabolites during the development of NAFLD have been gradually revealed. Bile acid (BA) is the main endpoint of cholesterol metabolism in the body. In addition, it also acts as a signaling factor t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 66 publications
1
9
0
Order By: Relevance
“… 60 Except for liver cancer, alterations in bile acid homeostasis could also be led by other hepatobiliary diseases, such as liver fibrosis, cirrhosis, and NAFLD. 11 , 61 , 62 Nevertheless, we observed similar associations in participants without prevalent hepatobiliary diseases. This suggested that the associations between circulating bile acids and liver cancer risk might not be solely attributed to these diseases.…”
Section: Discussionsupporting
confidence: 67%
“… 60 Except for liver cancer, alterations in bile acid homeostasis could also be led by other hepatobiliary diseases, such as liver fibrosis, cirrhosis, and NAFLD. 11 , 61 , 62 Nevertheless, we observed similar associations in participants without prevalent hepatobiliary diseases. This suggested that the associations between circulating bile acids and liver cancer risk might not be solely attributed to these diseases.…”
Section: Discussionsupporting
confidence: 67%
“…The treatment of NAFLD by interfering with BA synthesis and metabolism has become a new research direction. But we didn’t find BA metabolism enriched pathway in our results 47 . These data showed that the BA metabolism was not the main process in development of DILI.…”
Section: Discussionmentioning
confidence: 65%
“…BAs play a crucial role in clearing cholesterol and preventing the buildup of harmful substances, such as TG, cholesterol, and toxic compounds, which can cause damage to the liver and other organs . Additionally, BAs also function as signaling molecules that regulate metabolism and inflammation and contribute to the inflammatory response in both liver and other tissues . In our study, we analyzed fecal samples to investigate changes in the profile of BA metabolites.…”
Section: Discussionmentioning
confidence: 99%